Kyoto-Mechanismen und globaler Klimaschutz: Die Rolle handelbarer Emissionsrechte - Stefan Bayer; Dieter Cansier (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1999)
– We analyze the Kyoto-mechanisms with respect to their possible impacts on the fulfillment of each country's reduction obligation and cost-efficiency. We conclude that an emissions trading system cannot be realized because it demands global harmonization of environmental policy in all countries. Joint implementation- and clean development mechanism-measures as well as bubbles can be used to slightly align different marginal abatement costs. However, our analysis shows complications when the clean development mechanism is used. These lead to an unsolvable conflict between the global reduction target and cost-efficiency. On the whole, the lion's share of the committed emissions reductions has to be undertaken in each Annex-B-country domestically.
urn:nbn:de:bsz:21-opus-21167
Keywords: 330